The Effectiveness of Guided Discovery Practicum Method in Global Warming Materials to Improve Students’ Critical Thinking Skills - Erwinsyah - Nurhidayat; Bayu - Widiyanto; Mobinta - Kusuma (Indonesian Journal of Science and Education (IJOSE), 2021)
The purpose of this research is (1) to determine the effectiveness of the guided discovery practicum method on global warming material to improve students' critical thinking, and (2) to determine the profile of students' critical thinking skills using the guided discovery practicum method on global warming material. This study is a quantitative study using a pretest-posttest control group design. The population of this study was class VII students at SMP Negeri 14 Tegal City in the 2019/2020 academic year as many as 58 students. The sampling technique used simple random sampling and obtained 24 students in class VII C as the experimental class and class VII B as many as 24 students as the control class. The results showed that: (1) the guided discovery practicum method in science learning had an effect on students' critical thinking skills, this was seen from the average value of the final ability test (posttest) in the experimental class of 77.75 and the average score in the experimental class. control of 70.00. and (2) the application of the guided discovery practicum method in the experimental class in the quite effective category in improving students' critical thinking skills. This can be seen from the average N-Gain value in the experimental class of 57.17%. Meanwhile, the control class that did not use guided discovery was less effective. This can be seen from the average value of N-Gain in the control class of 43.18%.Keyword: Guided discovery practicum method, critical thinking skills